2016
DOI: 10.1371/journal.pone.0149806
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Drug-Resistant Tuberculosis in Papua New Guinea: Results of a Large Population-Based Survey

Abstract: BackgroundReliable estimates of the burden of multidrug-resistant tuberculosis (MDR-TB) are crucial for effective control and prevention of tuberculosis (TB). Papua New Guinea (PNG) is a high TB burden country with limited information on the magnitude of the MDR-TB problem.MethodsA cross-sectional study was conducted in four PNG provinces: Madang, Morobe, National Capital District and Western Province. Patient sputum samples were tested for rifampicin resistance by the Xpert MTB/RIF assay and those showing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 6 publications
0
39
1
Order By: Relevance
“…Our estimate for the Balimo region is higher than the previous Western Province region incidence estimate of 549 cases per 100 000 people per year . The South Fly District and the provincial capital of Daru have previously been noted for having a high burden of TB, and particularly DR‐TB . A heavy burden of TB cases in the North Fly District has previously been observed, while more recent research described 18 cases of TB from Tabubil, with one of these identified as rifampicin resistant .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our estimate for the Balimo region is higher than the previous Western Province region incidence estimate of 549 cases per 100 000 people per year . The South Fly District and the provincial capital of Daru have previously been noted for having a high burden of TB, and particularly DR‐TB . A heavy burden of TB cases in the North Fly District has previously been observed, while more recent research described 18 cases of TB from Tabubil, with one of these identified as rifampicin resistant .…”
Section: Discussionmentioning
confidence: 95%
“…The South Fly District and the provincial capital of Daru have previously been noted for having a high burden of TB, and particularly DR-TB [2][3][4][5][20][21][22]. A heavy burden of TB cases in the North Fly District has previously been observed, while more recent research described 18 cases of TB from Tabubil, with one of these identified as rifampicin resistant [4,5]. The data from the North Fly District, in combination with the Middle Fly District data described in our study, highlight the broad reach of TB across Western Province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Given the limited access to drug susceptibility testing in PNG, Xpert offers a critical contribution not only to TB diagnosis but also to rapid detection of drug resistance in this setting. There were operational challenges to executing screening using both smear microscopy and Xpert.…”
Section: Public Health Actionmentioning
confidence: 99%
“…Papua New Guinea (PNG) has a high rate of drug resistant TB in its Western Province (22, 23). We recently characterized a drug resistant tuberculosis outbreak on Daru island, which is driven by a modern Beijing sub-lineage 2.2.1.1 strain (24).…”
Section: Introductionmentioning
confidence: 99%